Overexpression of the PDZ1 Domain of PDZK1 Blocks the Activity of Hepatic Scavenger Receptor, Class B, Type I by Altering Its Abundance and Cellular Localization - Fenske, Sara A. (American Society for Biochemistry and Molecular Biology, 2008)
PDZK1 is a four-PDZ domain-containing scaffold protein that, via its first PDZ domain (PDZ1), binds to the C terminus of the high density lipoprotein (HDL) receptor scavenger receptor, class B, type I (SR-BI). Abolishing PDZK1 expression in PDZK1 knock-out (KO) mice leads to a post-transcriptional, tissue-specific decrease in SR-BI protein level and an increase in total plasma cholesterol carried in abnormally large HDL particles. Here we show that, although hepatic overexpression of PDZK1 restored normal SR-BI protein abundance and function in PDZK1 KO mice, hepatic overexpression of only the PDZ1 domain was not sufficient to restore normal SR-BI function. In wild-type mice, overexpression of the PDZ1 domain overcame the activity of the endogenous hepatic PDZK1, resulting in a 75% reduction in hepatic SR-BI protein levels and intracellular mislocalization of the remaining SR-BI. As a consequence, the plasma lipoproteins in PDZ1 transgenic mice resembled those in PDZK1 KO mice (hypercholesterolemia due to large HDL). These results indicate that the PDZ1 domain can control the abundance and localization, and therefore the function, of hepatic SR-BI and that structural features of PDZK1 in addition to its SR-BI-binding PDZ1 domain are required for normal hepatic SR-BI regulation.